Electric Mobility and Tourism – Designing a Model for Charging Infrastructure in Seasonal Tourism Regions - Bongard, Stefan; Friesenhahn, Andreas (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The growing share of battery electric vehicles (BEVs) poses new challenges for tourism regions, which are typically characterized by strong seasonality. Charging infrastructure must be sufficiently dimensioned to meet peak demand during the high season, while utilization drops sharply in the low and off-season, raising concerns about economic viability. This paper develops a modeling framework that calculates a seasonal charging coverage ratio and integrates an economic efficiency analysis. Using a case study of a summer destination on the southern European coast, the model quantifies seasonal charging demand, infrastructure capacity, and key economic parameters. The results reveal a structural imbalance: demand during the high season approaches infrastructure capacity, while extended periods of low demand create significant overcapacity and insufficient utilization. Consequently, the charging infrastructure generates an overall annual loss. The proposed modeling framework provides a transferable analytical framework that supports evidence-based charging infrastructure planning in highly seasonal tourism destinations.